PERBANDINGAN INFILTRASI LAHAN TERHADAP KARAKTERISTIK FISIK TANAH, KONDISI PENUTUPAN TANAH DAN KONDISI TEGAKAN POHON PADA BERBAGAI JENIS PEMANFAATAN LAHAN - Sudarmanto, Arif; Buchori, Imam; Sudarno, Sudarno (Jurnal Geografi, 2014)
This research was conducted in Kreo Sub-watershed in Semarang and aimed toexamine the difference of soil physical characteristic in various land utilizationtypical and to examine the relationship among soil physical characteristic, soilcover and trees stand conditions to infiltration capacity. In this research, thepicking out of the soil specimens and the test of infiltration was conducted in 10(ten) kinds of land utilization in the same condition of slope, soil, land use, anddistribution of precipitation. The result of this research showed that there is asignificant difference among the condition of the texture, the porosity, and thepermeability, whereas the organic matter and the early capacity of water have nosignificant difference. Whereas adequate correlation was found among thepermeability, the early capacity of water and the soil cover condition, mean whilethe trees stand condition, the texture, the organic matter, and the porosity have nostrong correlation with infiltration capacity.